Relationship of Senior Perceptions of the Familiarization to the School Environment and Peer Social Support with Bullying of Juniors - Siti Wulan Sari; Firman Firman; Riska Ahmad (Universitas Negeri Padang, 2019)
Senior students bullying juniors is one of the problems related to senior perceptionsof the familiarization to the school environment and peer social support, and the purpose of this study was to reveal relationship between these variables. This study uses a correlational method and has a sample of 202 students, who were found using techniques Proportional Random Sampling. Data were collected using a scale measuring senior perceptionsof the familiarization to the school environment (31 valid items = 0.914), a scale measuring peer social support (29 valid items = 0.873), and scale measuringbullying to junior (29 items valid = 0.902). Data were analyzed by multiple regression, and the results showed a correlation coefficient R = 0.089 and p = 0.00 (p> 0.05). The results showed that there was a negative and significant relationship between senior perceptions of familiarization to the school environment and peer social support with bullying to juniors.